Mixed gonococcal infections in a high-risk population, Sydney, Australia 2015: implications for antimicrobial resistance surveillance? - Goire, Namraj; Kundu, Ratan; Trembizki, Ella; Buckley, Cameron; Hogan, Tiffany R.; Lewis, David A.; Branley, James M.; Whiley, David M.; Lahra, Monica M. (Journal of antimicrobial chemotherapy, 2017)
Previous studies have shown that mixed-strain gonococcal infections can occur. However, it remains unclear whether such infections impact upon the reliability of Neisseria gonorrhoeae antimicrobial resistance (AMR) surveillance. In this study, we aimed to resolve this question by intensively sampling isolates from gonorrhoea-positive specimens in a high-risk population in Sydney, Australia. A total of 615 N. gonorrhoeae isolates, originating from 63 clinical samples (31 rectal swabs and 32 throat swabs), were characterized. All isolates were subject to N. gonorrhoeae identification, antimicrobial susceptibility testing and genotyping by SNP-based MLST. Only 2 of the 63 (3.2%) samples provided evidence of mixed-strain infections. These comprised two rectal swabs that harboured isolates of different SNP-based MLST genotypes; however, the AMR susceptibility profiles of the different genotypes from these samples were indistinguishable. Within-sample differences in the AMR susceptibility profiles were observed for a further seven samples; however, the differences were not considered significant; MIC values were typically within a 2-fold difference or were close to test breakpoints. Results of this study provide further evidence that mixed-strain gonococcal infections do occur, although at low prevalence. Our data indicate that at a population level such infections are unlikely to impact significantly upon N. gonorrhoeae AMR surveillance.